2017
DOI: 10.21003/ea.v165-08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of devaluation on service sector exports in Saudi Arabia: non-linear ARDL approach

Abstract: Devaluation policy is considered as operative in raising the exports' performance in any country. This paper had investigated this issue in the non-linear Autoregressive Distributed Lag (ARDL) setting developed by Shin et al. (2014) to differentiate the devaluation and appreciation policy, and to verify symmetrical or asymmetrical effects. We investigated a period of 1970-2016 for the six major service sector exports of Saudi Arabia. In each model, world income, as well as positive and negative variables of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…For instance, Achy and Sekkat [8] augment exchange rate in the exports’ demand function of Algeria, Egypt, Morocco, Tunisia and Turkey and find a significant contribution of exchange rate. Later on, some other studies also find a significant effect of exchange rate on exports [9,10,11,12].…”
Section: Literature Reviewmentioning
confidence: 95%
“…For instance, Achy and Sekkat [8] augment exchange rate in the exports’ demand function of Algeria, Egypt, Morocco, Tunisia and Turkey and find a significant contribution of exchange rate. Later on, some other studies also find a significant effect of exchange rate on exports [9,10,11,12].…”
Section: Literature Reviewmentioning
confidence: 95%
“…Moreover, the effect of depreciation (PRER it ) is found to be larger than that of the effect of appreciation (NRER it ) in all estimates. Mahmood et al [59] also reported the asymmetrical effects of the exchange rates on trade in Saudi Arabia. We find mixed evidence of symmetry and asymmetry in the relationship between real exchange rates and trade balances.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetry is corroborated in the relationship of the real exchange rates and trade balances in all GCC countries. Mahmood et al [59] also reported the asymmetrical effect of the exchange rates on the service sector's exports in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Kurtovic, Halili, and Maxhuni (2017) showed the J-curve effect existence on the cases of Germany, Austria, and Croatia. Mahmood, Al Khateeb, and Ahmad (2017) found that depreciation of Saudi rial leads to increases of industrial exports. Fontagne, Martin, and Orefice (2018) indicated that the export price elasticity is larger than the exchange rate elasticity.…”
Section: Previous Studiesmentioning
confidence: 99%